ELECTRON MICROSCOPY OF ENTOMOPATHOGENIC FUNGAL INVASION ON THE CABBAGE-HEART CATERPILLAR CROCIDOLOMIA BINOTALIS ZELLER (LEPIDOPTERA: PYRALIDAE) - N. Hashim; Y.B. Ibrahim; Y.H. Tan (Universitas Gadjah Mada, 2002)
The infection on Crocidolomia binotalis Zeller by the entomopathogenic fungi Paecilomyces fumosoroseus (Wise) Brown and Smith, Beauveria bassiana (Bals.) Vuill, and Metarhizium anisopliae var. majus (Metsch.) Sorokin was studied histopathologically using electron microscopy. Conidia which landed on the cuticle germinated within four to six hours. In the case of B. basiana, shortly after landing, an appresorium was formed that attached itself fast onto the cuticle at the point of fungal entry. The infected larva then entered the moribund state 12 to 24 hours after inoculation. Death of the larva followed 24 to 48 hours later. By then the body cavity as well as the trachea were clogged with mycelia, and compacted masses conidiophores producing white conidia were found all over the larval cadaver one to two days later. P. fumosoroseus sporulated more abundantly on the surface of the cadaver compared to B. bassiana or M. anisopliae.